THE INFLUENCE OF RADICAL IDEAS ON THE POLITICAL CONSCIOUSNESS OF YOUNG PEOPLE - Turaev , Abror Salokhiddinovich (Educational Research in Universal Sciences, 2023)
In this article, the emergence of the ideology of radicalism and the factors of its development in the youth environment are discussed, the negative impact of youth radicalization on the political culture of the society and the factors of radicalization are analyzed.